The Succession Factor of Family Business: The Perspective of Successor - Agus Fernando; Dedi Kurniawan; Dani Lukman Hakim (Faculty of Business, President University, 2023)
Family businesses play a significant role in the global economy, accounting for over 61.25 % of the Gross Domestic Product. However, the survival rate beyond the third generation is only less than 10 %, highlighting the importance of successful succession for sustainable business. While previous research has identified various factors contributing to successful succession in family businesses, there has been limited focus on the perspectives of the successors themselves. This study aimed to examine factors related to successor readiness and explore challenges and success factors during the succession process from the viewpoint of family business successors. The research was conducted in Indonesia, involving seventyt successors from small and medium-sized family businesses in such as craft, retail, food and drink, and garment/fashion. The findings revealed the factors that contribute to successor readiness, including experience working in a different company, experience working in a family-owned company, specialized knowledge in the industry, industry-specific knowledge, individual preferences or personal necessities in working for the family business, dedication and loyalty to the company, financial incentives or monetary rewards, harmonious family dynamics, interpersonal relationships among family members, and trust in the successor's competence. Addressing these factors appropriately, both by the predecessors and the successors, will ensure the continuity of the family business into the future.